Progression of electronic and communication system for motion control of modular snake-like-robot (2021)
This Project consists of a development of an electronics system to manipulate a snake like robot in a modular way. The structure of this project is based on three topics; The Hardware and its Firmware, The Mathematical Analysis of the Serpenoid Curves and The Robotic Simulation. In regards to the first topic electronic cards were implemented in a master-slave relationship for joint control of each mechanical module, these cards are composed of a DSPIC30F4011, microchip 16-bit microcontroller that incorporates the CAN module, essential protocol for communication between cards, PWM outputs for motor control, analogue and digital ports; as well as a socket to connect to an external device through the UART. The firmware has been written in MikroC Pro. The mathematical analysis is based on the Hirose-Serpenoid curves, hence every microcontroller implements a characteristic equation from the Hirose curves to generate a serpentine movement and last but not least the snake like robot is simul ated using ROS (Robotic Operating System) in Rviz